Nitrogen Fertilizer Management Strategies for Rice Production in Bangladesh: Nitrogen Fertilizer for Rice Production - Ali Choudhury, Abu Turab Mohammad; Saleque, Mohammad Abu; Zaman, Shafiuddin Kaisar; Bhuiyan, Nurul Islam; Shah, Abdul Latif; Rahman, Mohammad Shamsur (Biological Sciences - PJSIR, 2013)